Training and history of patient loyalty in the context of private medical services - Barra, Cristóbal; Torres M, Eduardo; Vásquez-Parraga, Arturo Z. (Estudios de Administración, 2011)
Due to the increasing competitiveness in the medical activity, patients loyalty to doctors have become as a key factor in medical services management. The purpose of this study is to establish how satisfaction, trust and commitment affect patients’ loyalty to their doctor in the private health services context. Valid and reliable scales are built and a proposed theoretical model is proved through structural equations method. Results show that the best model to explain the formation of loyalty starts with satisfaction and it is mediated by trust and commitment, building a chain relationship. These results are supported by contrasting the proposed model with many other alternative models, concluding an optimal structure for loyalty formation based on the studied variables.